Islam and Open Society Fidelity and Movement in the Philosophy of Muhammad Iqbal - Diagne, Souleymane Bachir (Book collections on Project MUSE., 2010)
In the atmosphere of suspicion and anger that characterizes our time, it is a joy to hear the voice of Iqbal, both passionate and serene. It is the voice of a soul that is deeply anchored in the Quranic Revelation, and precisely for that reason, open to all the other voices, seeking in them the path of his own fidelity. It is the voice of a man who has left behind all identitarian rigidity, who has 'broken all the idols of tribe and caste' to address himself to all human beings. But an unhappy accident has meant that this voice was buried, both in the general forgetting of Islamic modernism an.